Histopathological analysis of male breast cancer in Southwestern Nigeria: A single-center retrospective study (2021)
Background: Breast cancer in men is still an uncommon and largely understudied disease. It accounts for 1% of all breast cancers. The aim of this study was to review all the male breast cancer cases diagnosed at the tertiary medical institution in South West Nigeria over a 10‑year period and to compare the findings with other similar studies done in Nigeria and globally. Methods: We retrospectively reviewed all histologically diagnosed cases of male breast cancers in the Department of Pathology, Tertiary Medical Institution in South West Nigeria over a 10‑year period from January 1, 2009, to December 31, 2018. Clinicopathological parameters including patients’ age, laterality, and specific histological sub‑types were extracted from surgical day book and Cancer Registry of the Department. The data were analyzed using the IBM SPSS Statistics (version 22; IBM Corporation, Armonk, New York, USA). The results were subsequently presented in tables, relative frequencies, group percentages, and photomicrographs. Results: Forty‑two cases of male breast cancer were seen, accounting for 1.7% of all breast cancer cases. The age range was between 22 and 91 years with a mean age of 60.3 years, and a peak occurrence was in the 8th decade. The right breast was more affected than the left, accounting for 52% of the total number of cases seen. The most common histological sub‑type found was invasive ductal carcinoma, accounting for 88% of all the cases. Conclusion: Male breast cancer is relatively uncommon compared to female breast cancer. It is more common in the older age group, and invasive ductal carcinoma is still the most common histological subtype.